The effects of explicit and implicit phonetic and phonological instruction on the intelligibility and comprehensibility: a study of teaching english pronunciation in the Pakistani context - , Ghulamullah (2019)
English language has been established as World Englishes but millions of non-native English speakers face problems due to unintelligibility and incomprehensibility. This problem exists globally and locally, which is partly because of the marginalisation of the teaching of pronunciation. The current study was carried out in the Pakistani context where deficiency in English language is rampant. The purpose of the study was to investigate whether explicit phonetic and phonological instructions are more effective that the implicit instruction. Two experimental groups were randomly selected in which each group consisted of 17 subjects. There were two independent variables (the explicit phonetic and phonological instructions versus the implicit instruction) and two dependent variables (intelligibility and comprehensibility). Each group was treated with a special treatment and was pretested and posttested. Intelligibility was measured by two experts from a Pakistani university using a 9-point Likert scale, while comprehensibility was evaluated through the IELTS listening test. The data was computed using an Independent Samples t-test and a Paired Samples test to see the difference between the means of both groups. The inter groups means difference between Group A and B for intelligibility and comprehensibility was statistically significant. The results indicate that the group who received the explicit phonetic and phonological instructions outperformed the group who was treated with the implicit instruction. Furthermore, a questionnaire survey was conducted to explore the opinions of the subjects about the study in which most on them agreed that they were unaware of sounds and prosodic features before the treatment. They also believe that the teaching of pronunciation should be included in the content and assessment at school in Pakistan. The current study may be a milestone in solving the intelligibility and comprehensibility problems in the Pakistani context promoting teaching pronunciation via explicit instruction.